Locating Relict Sinter Terrace Sites at Lake Rotomahana, New Zealand, With Ferdinand von Hochstetter's Legacy Cartography, Historic Maps, and LIDAR - Lorrey, Andrew Martin; Woolley, John-Mark (Frontiers in Earth Science, 2018)
Te Otukapuarangi (the Pink Terrace), Te Tarata (the White Terrace) and Te Ngāwhā a Te Tuhi (the Black Terrace) were massive siliceous sinter formations at Lake Rotomahana, New Zealand, that were ostensibly lost in the catastrophic 1886 Tarawera eruption. Previous work using an unpublished watercolour map and notes by Ferdinand von Hochstetter (1829-1884) have recently supported claims that the former Pink and White Terraces survived the 1886 eruption, and that they may be located under tephra adjacent to the modern lake margin. Divergent perspectives about the fate of Lake Rotomahana’s former sinter terraces suggest the reconstruction of New Zealand’s largest historic volcanic eruption is incomplete. We harnessed a wider amount of unique historic data recorded during Hochstetter’s 1859 survey than previously reported to hone the locations of the former Rotomahana sinter terraces. Volcanic landforms, the physical geography of the countryside, and former settlements are tied together via common sightings between sequential survey datums. Light detection and ranging (LIDAR) data supported the reconstruction of Hochstetter’s former survey and datum locations. Of significance, shared landmarks between the survey stations increased the confidence for resecting the 1859 datum position on the southern margin of former Lake Rotomahana. Hochstetter’s survey watercolour maps are part of a series drafted prior to a final version being professionally printed, and they do not portray a spatially accurate depiction of how sinter terraces and geothermal features around former Lake Rotomahana were arranged. As such, assertions of their superior cartographic nature are not well-founded, and application of them to provide former Terrace locations is compromised. The published pre-eruption map of Lake Rotomahana validates well against Hochstetter’s field diary measurements. When Hochstetter’s published map is orientated using reconstructed positions for survey datums at Lake Rotomahana, the former locations of the White and Pink Terraces lie entirely within the modern boundaries of the lake and not on land. The Black Terrace may have been destroyed and/or converted to an eruption crater, but may still exist on land (intact or in-part) west of Lake Rotomahana’s modern shoreline. This study demonstrates the value of historic cartography to improve understanding of volcanic processes.